2004
DOI: 10.1002/ajmg.b.30035
|View full text |Cite
|
Sign up to set email alerts
|

Lack of relationship between CO2 reactivity and serotonin transporter gene regulatory region polymorphism in panic disorder

Abstract: Changes in the function of the serotonergic system influence both panic phobic symptoms and carbon dioxide (CO2) reactivity in patients with panic disorder. Schmidt et al. [2000: J Abnorm Psychol 109(2):308-320] recently reported a predictive role of the genetic variants of the 5-HTTLPR on the fearful response to CO2 in healthy controls. We tested the hypothesis that the heterogeneity of CO2 reactivity in patients with panic disorder could be related to the allelic variation of the 5-HTT promoter. Ninety-five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Also Schmidt et al (2000) reported that subjects homozygous for the long variant were at greater risk for behavioral hyper-reactivity to 35% CO 2 challenge than those with short-allele genotypes. On the contrary, in patients with PD, CO 2 reactivity was not influenced by 5-HTTLPR genetic variants (Perna et al, 2004). On the other hand, the long-allele variant of 5-HTTLPR has been associated with a better response to SSRI treatment in females with PD (Perna et al, 2005).…”
Section: -Htt Genementioning
confidence: 86%
“…Also Schmidt et al (2000) reported that subjects homozygous for the long variant were at greater risk for behavioral hyper-reactivity to 35% CO 2 challenge than those with short-allele genotypes. On the contrary, in patients with PD, CO 2 reactivity was not influenced by 5-HTTLPR genetic variants (Perna et al, 2004). On the other hand, the long-allele variant of 5-HTTLPR has been associated with a better response to SSRI treatment in females with PD (Perna et al, 2005).…”
Section: -Htt Genementioning
confidence: 86%
“…These polymorphisms have been found in two meta‐analyses to have a small but statistically significant association with bipolar disorder (191, 192), and in one study specifically with rapid cycling bipolar disorder (193). Although there are no positive reports in panic disorder, there is evidence that a SERT polymorphism is associated with panic vulnerability to cholecystokinin‐induced (194) but not carbon dioxide‐induced panic attacks (195). The SERT polymorphism has also been associated with increased emotional reactivity and excitation of the amygdala (196–198).…”
Section: Molecular Correlates Of Bipolar Panic and Plasticitymentioning
confidence: 99%
“…A study in healthy volunteers showed that the LL genotype (homozygous for the L-allele) predicted a greater fearful response to a single 35% CO 2 inhalation (Schmidt et al, 2000). Although this result could not be replicated in patients with PD (Perna et al, 2004), the same researchers demonstrated that the presence of the L-allelic variant was associated with a better therapeutic response to the serotonin reuptake inhibiting drug paroxetine in PD (Perna et al, 2005).…”
Section: Introductionmentioning
confidence: 99%